Representations of Childhood and “Modes of Address” in Palestinian and Pan-Arab Programs for Children - Awan, Feryal (Children, Youth, and International Television, 2022)
This chapter explores the ways in which the portrayal of children in Palestinian screen content compares with the positioning of children in leading pan-Arab children’s channels. Using critical discourse analysis, it compares the definition and representation of childhood in three Arabic language texts (two magazine shows and one animation), and examines the ways in which the texts construct narratives of childhood and whether they reproduce or challenge hegemonic definitions of childhood. The chapter analyses the language used to address the child audience and the ways in which adult–child relations are depicted. The chapter concludes that while there are some characteristics unique to Palestinian programming, the positioning of children and the “modes of address” are similar in all three programmes, and there are common assumptions and idealizations of childhood. However, there is some evidence that the Emirati animation analysed challenges dominant (adult-generated) definitions of childhood present in Arab societies by presenting childhood as a dynamic space of empowerment
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Pakistan (corpus analysé); Royaume-Uni (lieu de production du savoir); _Nettoyé